ChemInform Abstract: Single‐Crystal Data of Ternary Germanides Ln2Nb3Ge4 (Ln: Sc, Y, Gd—Er, Lu) and Sc2Ta3Ge4 with Ordered Sm5Ge4‐Type Structure. Issue 38 (30th August 2013) - Reker, Bastian; Matar, Samir F.; Rodewald, Ute Ch.; Hoffmann, Rolf‐Dieter; Poettgen, Rainer
Abstract The title compounds are synthesized by arc melting of the respective elements in stoichiometric ratios (water‐cooled Cu crucible, 700 mbar Ar).